TECHNOLOGY FOR USING ELECTRONIC EDUCATION IN BIOLOGY CLASSES (Web of Teachers: Inderscience Research, 2025)
The article presents the role and objectives of digital educational resources, multimedia presentations, internet resources, electronic encyclopedias, didactic materials, and video and audio materials in teaching biology. Information is provided on the use of information and communication technologies in biology and the effective provision of the lesson process.